Avaliação da aprendizagem de alunos com deficiência intelectual: a experiência de professores do ensino fundamental em Jijoca de Jericoacoara-CE - Muniz, Sheila Maria (2018)
Contemporary society faces the challenge of Inclusive Education, since it recommends the ideals of equality and quality in Education, universally. Therefore, the inclusion of students with disabilities in mainstream education involves curricular adaptations and significant changes in the practice of learning evaluation, because this practice traditionally bases on classification, selection and exclusion, as opposed to the formative process recommended by the Law of Guidelines and Bases of National Education (LDB 9394/96). In this perspective, this research aimed to investigate the practice of learning evaluation with students with Intellectual Disability (ID) included in mainstream classes of Elementary Education of the municipal educational system of Jijoca de Jericoacoara-CE. The specific objectives of this study were: i) research the concepts of the teachers about Intellectual Disability, Educational Inclusion and Learning Evaluation; ii) identify the procedures and instruments that teachers use to evaluate the students with ID; iii) know the difficulties relating to the learning evaluation of students with ID through teachers, students and their relatives or guardians; and iv) collect suggestions from the teacher, students and their relatives or guardians in order to improve the learning evaluation of this students. The perspective of Vianna (2014, 2005, 2000, 1989) concernig to the historical course of Educational Evaluation, the insights of Beyer (2005) in relation to the inclusion and evaluation of students with ID, and the viewpoint of Hadji (2001) on the formative evaluation substantiated the theoretical input. Thus, we are dealing with a qualitative research. We used interviews, semi-structured questionnaires, documentary analysis and observations to collect data. We gathered the data in units of meaning and we analyzed them in the light of Heidegger's hermeneutics. Six teachers, four pedagogical coordinators, three school principals and four relatives of the students with ID composed the samples, totaling 17 subjects. The results indicated that the school environment where these children are still not fully adapted to their specificities, preventing the inclusion. The main difficulties pointed out by the subjects concerned to the lack of continuous training directed to the theme of inclusion, as well as learning evaluation of the students with ID and limited conceptions about Inclusive Education.